Interactive Activities as an Alternative to Encourage Students Involvement in English Reading Class - Kusrini, Endang (EDUCARE, 2012)
ABSTRACT: The common problem found in reading was the students could not comprehend the text easily, because the students were passive. They never worked together in discussion or presentation. When the teacher asked them to read some texts and to find out the main ideas from the texts, most of the student could not or it easily. An interactive activity as a technique that is possible for them to improve their involvement in learning English, especially in reading class. This technique can help the students to comprehend the content of reading text in group; beside that, they can share, cooperate, and support each other, achive learning objective, and make the learning enjoyable. Interactive activities will help the teacher to engage the students. Teacher can use interactive activities in classrooms from high school to university. The choice of strategies is affected by a number of considerations: the level of the objectives, the abilities of the students, teacher teaching skills and preferences, the size of the class, and many other factors. However, since school is supposed to help students sharpen their higher-order thinking skills, strategies that promote active involvement in learning should be the goal of every teacher. Interactive lecturing and structured discussions are methods that promote a degree of student involvement. KEY WORDS: Interactive activities, teaching-learning process, involvement the student, and reading comprehension in English.About the Author: Endang Kusrini, M.Hum. is a Lecturer at the Department of English Education, Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, P.O. Box 202, Purwokerto, Central Java, Indonesia. She can be reached at: endang_kusrini@yahoo.comHow to cite this article? Kusrini, Endang. (2012). âInteractive Activities as an Alternative to Encourage Students Involvement in English Reading Classâ in EDUCARE: International Journal for Educational Studies, Vol.4(2) February, pp.191-200. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 11, 2011); Revised (January 24, 2012); and Published (February 17, 2012).